Iron-catalyzed arene C−H hydroxylation - Cheng, Lu; Wang, Huihui; Cai, Hengrui; Zhang, Jie; Gong, Xu; Han, Wei (Science (American Association for the Advancement of Science), 2021)
Although iron-dependent enzymes efficiently hydroxylate aryl rings, this activity has proven hard to replicate with synthetic catalysts. Cheng et al . report that a disulfide ligand activates iron to catalyze carbon–hydrogen hydroxylation of a wide variety of arenes using hydrogen peroxide. The protocol can also cleanly functionalize phenols with an additional hydroxyl group, although unfunctionalized arenes react more rapidly, in contrast to conventional oxidative selectivity patterns. The authors showcase this complementary selectivity through hydroxylation of pharmaceuticals with complex substitution patterns. —JSY An iron complex coordinated by a disulfide ligand catalyzes selective hydroxylation of arenes with hydrogen peroxide. The sustainable, undirected, and selective catalytic hydroxylation of arenes remains an ongoing research challenge because of the relative inertness of aryl carbon-hydrogen bonds, the higher reactivity of the phenolic products leading to over-oxidized by-products, and the frequently insufficient regioselectivity. We report that iron coordinated by a bioinspired l -cystine–derived ligand can catalyze undirected arene carbon-hydrogen hydroxylation with hydrogen peroxide as the terminal oxidant. The reaction is distinguished by its broad substrate scope, excellent selectivity, and good yields, and it showcases compatibility with oxidation-sensitive functional groups, such as alcohols, polyphenols, aldehydes, and even a boronic acid. This method is well suited for the synthesis of polyphenols through multiple carbon-hydrogen hydroxylations, as well as the late-stage functionalization of natural products and drug molecules.